Religiosity and modesty: how veiled Muslim women in the United States define modest activewear. Issue 2 (3rd May 2020) - Hwang, Chanmi; Kim, Tae Ho
ABSTRACT: The purpose of this study was to explore 1) how veiled Muslim in the United States define modest activewear and their barriers to purchasing this clothing, and 2) how consumers' purchasing behaviors differ in accordance with the extent of religiosity (high vs. low), based on the extended theory of planned behavior. The most important attribute of modest activewear for the women participating was appropriate concealment, in terms of longer length, loose fit, and fabric thickness. The study found that the level of religiosity influenced consumers' purchasing behaviors. The findings suggest that there is a need for designing a range of appropriate modest clothing targeting both casual and devout Muslim women, and to contribute to the understanding of this growing consumer segment so that activewear brands can better design their products to appeal to Muslim women's standards and needs.